Effects of single-tree selective harvest method on ecosystem services in a mixed temperate broadleaf forest in Iran - Karamdoost Marian, B.; Alijanpour, A.; Banj Shafiei, A.; Sasanifar, S.; Álvarez-Álvarez, P. (Frontiers in Forests and Global Change, 2024)
IntroductionThis study examines the effects of the single-tree selective harvesting method on ecosystem services in a mixed temperate broadleaf forest in Iran. Key indicators such as carbon sequestration, tree species diversity, soil nutrient cycling, and stand volume are analyzed, emphasizing their significance for sustainable forest management.MethodsThe research was conducted in four districts, each comprising two parcels: one managed using the single-tree selective harvesting method and the other serving as a control. Data on ecological and biodiversity parameters were collected, and statistical analyses, including two-way ANOVA and Principal Component Analysis (PCA), were performed to assess the impact of management practices.ResultsThe findings reveal that the single-tree selective harvesting method significantly influences regulating and supporting ecosystem services. Carbon storage varied with elevation, affecting both soil and forest floor litter. Tree species diversity increased, with more species present and a reduction in dominance by certain species. However, this method also resulted in reduced stand volume in the managed areas. Elevation significantly impacted diversity indices, litter carbon storage, available potassium, and stand volume. Additionally, the interaction between management and elevation was significant for soil carbon storage, richness, diversity, total nitrogen, available potassium, and stand volume.DiscussionThe single-tree selective harvesting method appears to be a viable forest management strategy for preserving ecosystem services in mixed temperate broadleaf forests, maintaining ecosystem health without significant negative effects on soil. However, careful consideration of site-specific ecological conditions and trade-offs between provisioning and regulating services is crucial. These findings have important implications for sustainable forest management in Iran and similar forest ecosystems globally.